ENHANCING THE MEASUREMENT ACCURACY OF THERMOSTATS AND DRYING CABINETS. - Gaibnazarov Boburjon Usmonjon ugli (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This thesis is dedicated to enhancing the metrological control of thermostats and drying cabinets. Based on an analysis of existing standards (GOST, ISO, O‘zDSt), shortcomings were identified, and new methods (multi-point calibration, digital sensors) were developed. The scientific novelty lies in the normative projects and IoT integration. The practical significance is in increasing measurement accuracy and ensuring safety.